Integrated reporting, risk-taking and firm performance: evidence from Malaysia / Benedict Valentine Arulanandam, Khakan Najaf and Susela Devi K Suppiah - Arulanandam, Benedict Valentine; Najaf, Khakan; K Suppiah, Susela Devi (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
Integrated Reporting (IR) has gained traction and momentum globally. The need to have a holistic reporting structure has culminated from the stakeholders' demands for financial and non-financial matrix. This study extends the empirical evidence on how integrated reporting has benefited corporate risk-taking and the Malaysian public listed firms' performance. We conducted a content analysis of 50 firms that adopted IR and 50 non-IR adopters. We identified IR adopters using the Bloomberg database and based on the six capitals listed in the IR framework: natural capital, social and relationship capital, intellectual capital, human capital, financial capital, and manufactured capital. This study adopts the value creation theory and enlightened value maximization theory perspectives, which posit that IR creates value through business models, releasing the value embedded in each type of capital. Our findings revealed that IR firms that undertook higher financial risk led to better financial and market-based performance as compared to non-IR counterparts. More importantly, our findings imply that IR adopters possess higher corporate governance quality and are able to manage higher risk tolerance. Our sensitivity and industry sub-sample analyses corroborate our main results. This study supports a significant impetus for regulators and policymakers to inspire the adoption of IR and to equip the stakeholders in the financial reporting supply chain with quality information.